2022
DOI: 10.1088/1742-6596/2244/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

RF power transfer efficiency of H ion sources: fluid modeling of accelerator source geometries

Abstract: The plasma in RF driven negative hydrogen ion sources is sustained via inductive coupling with large power levels of up to 100 kW and low frequencies around 1 MHz. This leads to currents of around 100 A flowing over the RF coil and corresponding voltages in the kV range. The associated risk of arcing limits the reliability of the whole ion source. The required power level can be reduced via optimizing the RF power transfer efficiency η, which is typically only in the range of 50 to 60% for H- sources used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…The CAD drawing as shown in figure 1(a) serves as a basis for the simulation domain of the 3D electromagnetic model, where only the driver region is included. The details of this model are discussed elsewhere [30].…”
Section: General Modeling Approach and Simulation Domainmentioning
confidence: 99%
See 3 more Smart Citations
“…The CAD drawing as shown in figure 1(a) serves as a basis for the simulation domain of the 3D electromagnetic model, where only the driver region is included. The details of this model are discussed elsewhere [30].…”
Section: General Modeling Approach and Simulation Domainmentioning
confidence: 99%
“…Note that for the validation the experimentally determined network resistance R net is used, since the geometry of the experimental setup does not change during the validation studies. For a detailed discussion on the modeling of the network losses in the ITER RF prototype ion source, see [30].…”
Section: Model Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…This RF-coil should be placed as close to the plasma as possible to maximise the coupling efficiency. Previous measurements found that the coupling efficiency of fusion ICPs is around 40%-50%, whereas the smaller RF-coils of accelerator-type ICPs were predicted to yield efficiencies closer to 80% [8]. The difference was attributed to the increased network resistance in fusion ICPs owing to the use of a Faraday shield to suppress capacitive coupling, which protects the dielectric from plasma sputtering.…”
Section: Introductionmentioning
confidence: 99%